Appropriation of rural microcredit in BrazilianNortheast: the function of animals in the production and economic system of families in a region at Pernambuco state - Desconsi, Cristiano; Aparecida Pacífico, Daniela (Universidade Federal Rural do Rio de Janeiro, 2016)
This article has the goal to analyze the process by family farmers in Brazilian northeast have been appropriated the rural microcredit (Pronaf B). To this, we want to understand the different calculations present, respectively, in the ownership and operation of public policy, from the study of twenty five cases in a region at Pernambuco state, Brazil. In these analysis, take the projects for farm loan and the function that livestock perform in the families’ economies. The anthropological approach used to analyze the rural microcredit attentive to the strategies of appropriation of farmers and the calculations implicit in them allowed us to go beyond the conventional analysis parameters and to understand how this public pol icy has incorporated in the logic of family farming reproduction in the Brazilian Northeast, strengthening this one.